Pengembangan Perangkat Pembelajaran IPA Pada Pokok Bahasan Tata Surya - Muhammad Rifansyah; Mastuang Mastuang; Abdul Salam M. (Universitas Lambung Mangkurat, 2017)
Learning materials used on the learning process in schools still considered not optimal and need to be developed. The impact of this is low cognitive results of students and consequently still need to be improved. Based on that, development of a learning equipment using a cooperative learning model conducted, which has specific purposes to describe: (1) validity of the learning equipment, (2) the practicability of learning equipment based on how it carrying out lesson plan, (3) the effecticeness of learning equipment based on student's cognitive achievement. The research stated: (1) learning equipment is considered valid with a good criteria, (2) the practicability of learning equipments are rated to be implemented very well, (3) the effectiveness of learning equipments has a high criteria. Based on the result of the research can be concluded that the natural science learning equipment which developed is viable for use in learning process.